2021
DOI: 10.1016/j.scitotenv.2020.142588
|View full text |Cite
|
Sign up to set email alerts
|

Different inactivation behaviors and mechanisms of representative pathogens (Escherichia coli bacteria, human adenoviruses and Bacillus subtilis spores) in g-C3N4-based metal-free visible-light-enabled photocatalytic disinfection

Abstract: Continuous economic loss and even human death caused by various microbial pathogens in drinking water call for the development of water disinfection systems with the features of environmentally friendly nature, high inactivation efficacy without pathogen regrowth, facile disinfection operation and low energy consumption. Alternatively, g-C 3 N 4 -based visible-light-enabled photocatalytic disinfection can meet the above requirements and thus has attracted increasin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(9 citation statements)
references
References 48 publications
(55 reference statements)
0
9
0
Order By: Relevance
“…In addition, the inactivation ability of the g-C 3 N 4 /vis system against viruses, bacteria, and spores could be enhanced by the addition of hydrogen peroxide (H 2 O 2 ) and peroxymonosulfate (PMS). 33 It has been revealed that the addition of H 2 O 2 produced ˙OH, which reacted with the protein coating of the target virus and caused irreversible modification, thus improving the antiviral ability of the system, and PMS was more conducive to the inactivation of bacteria. Moreover, considering the good biocompatibility of g-C 3 N 4 , it is a potential choice to apply it to the agricultural field for the inactivation of plant pathogens.…”
Section: Metal-free Photocatalysts For Disinfectionmentioning
confidence: 99%
“…In addition, the inactivation ability of the g-C 3 N 4 /vis system against viruses, bacteria, and spores could be enhanced by the addition of hydrogen peroxide (H 2 O 2 ) and peroxymonosulfate (PMS). 33 It has been revealed that the addition of H 2 O 2 produced ˙OH, which reacted with the protein coating of the target virus and caused irreversible modification, thus improving the antiviral ability of the system, and PMS was more conducive to the inactivation of bacteria. Moreover, considering the good biocompatibility of g-C 3 N 4 , it is a potential choice to apply it to the agricultural field for the inactivation of plant pathogens.…”
Section: Metal-free Photocatalysts For Disinfectionmentioning
confidence: 99%
“…The technology of photocatalysis that employs carbon-based photocatalyst has attracted much attention due to the zero risk of metal leaching into the water system and optimum natural light-harvesting capability [ [77] , [78] , [79] ]. The non-metal photocatalysts that have been developed for virus disinfection include carbon-based materials such fullerene [ 80 , 81 ] carbon nanotube [ 82 ], carbon dot [ 83 , 84 ], and graphitic carbon nitride (g-C 3 N 4 ) [ 78 , 85 , 86 ].…”
Section: Virus Disinfection Via Photocatalysismentioning
confidence: 99%
“…In contrast to conventional disinfection methods, photocatalytic disinfection showcases extensive bactericidal effectiveness [ 18 ], simultaneously addressing a variety of microorganisms such as bacteria, viruses, and fungi. The notable advantage lies in the lack of chemical residues after treatment, minimizing adverse impacts on both the environment and human health [ 19 ]. Moreover, the sustainability of the photocatalytic disinfection process is noteworthy, as it only requires a light source to activate the catalyst, eliminating the necessity for frequent chemical replacements or additions.…”
Section: Introductionmentioning
confidence: 99%